The Principal's Approach to Improving Teacher Performance at SDN Sumur Dalam Based on Local Wisdom - Muhammad Ainul Yaqin; Lailatul Jannah (Tarbiyatuna Kajian Pendidikan Islam, 2025)
This research aims to analyze the principal's strategy in improving teacher performance at primary school based on local wisdom. School principals have a central role in creating a conducive work environment and encouraging teachers to improve their professionalism and teaching quality. The research method used is a descriptive qualitative approach, with data collection techniques through observation, interviews and documentation. The research results show that school principals implement various strategies based on local wisdom, such as building a work culture based on the values ​​of mutual cooperation, deliberation, and respect for teacher achievements. Apart from that, the school principal also provides support in the form of training, coaching and providing ongoing motivation. Internal and external factors that influence teacher performance are also analyzed to find more effective solutions. The implication of this research is the importance of adaptive and innovative school principal leadership in improving the quality of education. With the right strategy, teacher performance can be improved significantly, thereby having a positive impact on the quality of learning and student achievement.